Anxiety Level of Final Year Students in the Preparation of Scientific Papers at the Faculty of Nursing UNTL, in 2024 - Oqui, Maximiano; Gomes, Lidia; Freitas, Felismina Maria; Freitas Moreira, Adriano; de Jesus Ximenes, Remígia Auxiliadora; Evaristo Obeno, Olandino; Geri de Sena Amaral, Saturnina Julieta (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Anxiety is a subjective state of human feeling and also is a reaction that occurs during an unknown. Based on data American College Health Association (2023) reported that anxiety and depression are common mental health problems for students with 36 % anxiety and 28 % to depression. Objective: The purpose of the research is to identify the student’s anxiety level about elaboration of final course work for the student 5th year at the School of Nursing of the Faculty of Medicine and Health Sciences of the National University Timor-Lorosa’e in the year 2024. Method: Research type is a descriptive quantitative method with a cross-sectional approach and technical probability sampling with Simple Random Sampling type. Result and Discussion: Research result indicated that majority the elaboration of final course work for the student mostly with poor elaboration category 29 (44%) and anxiety level mostly with severe category 25 (38%). The population for this research is 5th year students at the Higher School of Nursing of the Faculty of Medicine and Health Sciences of the National University Timor-Lorosa’e and the sample for this research is a total of 66 students. Data analysis used SPSS program to analyze the elaboration of final course work and the level of anxiety. Conclusion: The elaboration of final course work for student is in poor elaboration and the anxiety is in the severe level.